Analysis of the Atmospheric Effects on the Vicarious Calibration of LAPAN-A3/IPB Satellite Multispectral Camera in Jaddih Hill Madura - Salaswati, Sartika; Hakim, Patria Rachman; Syafrudin, A Hadi; Herawan, Agus; Hartono, Rommy; Utama, Satriya; Yatim, Rakhmat; Ardinal, Rifki; Pamadi, Bambang Sigit (Indonesian Journal of Aerospace, 2022)
Line Imager Space Application (LISA) is a multispectral camera on the LAPAN-A3/IPB satellite. This camera is the main payload that supports the remote sensing mission of the LAPAN-A3/IPB satellite. The important role of LISA requires this camera has a good quality standard. Vicarious calibration is one of the ways to get this quality. Vicarious calibration of LISA in the Jaddih hill area has been done, but the process has not used aerosol optical depth data. Therefore, further research was conducted to determine the effect of AOD data on the radiance coefficient. This paper describes the vicarious calibration of LISA using three types of data, namely LISA image data, reflectance data, and aerosol optical depth data of the Jaddih hill area. From the three data, the radiance coefficient for each LISA channel was obtained. The results show that there is an effect of AOD data on the radiance coefficient, but the effect is not too significant. The difference of the radiance coefficients for each channel is not too far away, that is 0.00008 for red channels, 0.00011 for green channels, 0.00039 for blue channels, and 0.00011 for NIR channels. Besides, the results of the radiance coefficient from previous studies indicate that the radiance coefficient is generated from this study is quite precise so that it can be applied for LISA imagery.